Attitudes of Science Teachers towards Development of Physical Concepts using Virtual laboratories and their Obstacles - Al-Otibi, Abdullah Sahal (Journal of Educational and Psychological Sciences, 2023)
This study aimed to identify the attitudes of science teachers towards developing physics concepts using virtual labs and their constraints in the Dawadmi governorate. To achieve the objectives of the study, the researcher used a descriptive survey method and prepared a questionnaire consisting of (31) phrases as a tool for the study. The study population consisted of (250) science teachers for all stages of public education in the Dawadmi governorate for the academic year 1443 AH, while the selected sample was randomly chosen from (150) teachers. The results showed that the attitudes of science teachers towards developing physics concepts using virtual labs in the Dawadmi governorate were highly positive with an average of (4.69 out of 5). The sample members had a great interest in using virtual labs to develop physics concepts with an average of (4.04 out of 5). The constraints of using virtual labs were also found to be high with an average of (4.35 out of 5). The study also showed no statistically significant differences attributed to the variable of teaching experience, while there were statistically significant differences between the estimates of the study sample members' attitudes towards using virtual labs attributed to the gender variable (male, female) in favor of females, and there were statistically significant differences between the averages of training course categories in favor of the category of two or more courses. Based on the study results, the researcher recommended intensifying training courses and programs for science teachers in the field of virtual labs, creating programs and applications for smart devices that contain virtual lab experiments, and linking scientific and physical concepts in the science curriculum content with virtual experiments.
Keywords: Science Teachers' Attitudes; Developing Physics Concepts; Virtual Labs